Correlation of serum S100B levels with brain magnetic resonance imaging abnormalities in children with status epilepticus - Prastiya Indra Gunawan; Darto Saharso; Dian Purnama Sari (Korean Pediatric Society, 2019)
Purpose To evaluate the association between elevated S100B levels with brain tissue damage seen in abnormalities of head magnetic resonance imaging (MRI; diffusion tensor imaging [DTI] sequence) in patients with status epilepticus (SE). Methods An analytical observational study was conducted in children hospitalized at Dr Soetomo Hospital, Surabaya, from July to December 2016. The patients were divided into 2 groups: SE included all children with a history of SE; control included all children with febrile seizure. Blood samples of patients were drawn within 24 hours after admission. SE patients also underwent cranial MRI with additional DTI sequencing. The Mann-Whitney test and Spearman test were used for statistical analysis. Results Fifty-three patients were enrolled the study. In the 24 children with SE who met the inclusion criteria, serum S100B and cranial MRI findings were assessed. Twenty-two children admitted with febrile seizures became the control group. Most patients were male (66.7%); the mean age was 35.8 months (standard deviation, 31.09). Mean S100B values of the SE group (3.430±0.141 μg/L) and the control group (2.998±0.572 μg/L) were significantly different (P<0.05). A significant difference was noted among each level of encephalopathy based on the cranial MRI results with serum S100B levels and the correlation was strongly positive with a coefficient value of 0.758 (P<0.001). Conclusion In SE patients, there is an increase of serum S100B levels within 24 hours after seizure, which has a strong positive correlation with brain damage seen in head MRI and DTI.